O roli bohatera w kreowaniu wywiadu prasowego (na przykładzie rozmów ze Sławomirem Mrożkiem) - Ślawska, Magdalena (Postscriptum Polonistyczne, 2020)
The article is of an analytical nature. The author explains the specificity of a press interview and the type of communication that is characteristic of this genre. She presents the participants of the interaction: the journalist and the interview hero. Here an unusual interview with Sławomir Mrożek published in „Duży Format” (addition to „Gazeta Wyborcza”) is recalled. The author refers to this text as an example of a game and specific communicative strategy. This example and fragments of some other interviews with Mrożek prove that the hero of the interview influences the creative character of the interview itself.